EVALUASI IMPLEMENTASI LIBRARY INFORMATION SYSTEM (UMSLibrary) DARI PERSPEKTIF MAHASISWA di UNIVERSITAS MUHAMMADIYAH SURAKARTA (UMS) - , Ari Triono; , I Wayan Mustika, S.T., M.Eng., Ph.D., ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Library Information System (UMSLibrary) is an information system used by UMS library for facilitating users. Library Information System (UMSLibrary) is used not only to browse the collection of books but also to do other activities, such as seeing a list of borrowed books, seeing late penalty, extend loan online and other functions. The development is done continuously by information technology (IT) team for 6 years but was not followed by an evaluation of the success of the system, hence until now the success of Library Information System (UMSLibrary) has never been evaluated. This study will evaluate the Library Information System (UMSLibrary) using a model of Success Seddon and Kiew, which was developed model by DeLone and McLean. Variables used in this model are the importance of the system, system quality, information quality, usefulness and user satisfaction. The sample for the questionnaire is distributed to 150 respondents and the acceptance amount of 144 questionnaires for analysis. Generalized Structured Component Analysis (GSCA), a web-based software GeSCA that can be accessed at the address http://sem-gesca.org, is used for analysis. Test results using Î± = 0.05 indicates that the system does not affect the quality of user satisfaction because the system manual instruction is not provided. The quality of the information does not affect the usefulness of the system because some of the information displayed by the system does not accompanied by manual instruction.